Pelatihan Penyembeliahan Hewan Qurban Pada Takmir Masjid Guna Penyediaan Daging Aman, Sehat, Utuh dan Halal (ASUH) - Suwarno; Wiwik Misaco Yuniarti; Trilas Sardjito; M. Anam Al Arif; Supriyadi (JPM: Jurnal Pengabdian Masyarakat, 2025)
Meat from qurban animals that are slaughtered halal and true, safe and common and decent for human consumption, will produce a taste of high quality. Meat may contain chemical residues, microbial contamination, and hazardous elements (hazard) that are harmful and disruptive to human health, so it is said that meat is a potentially hazardous food ingredient (potentially dangerous food = PHF). The purpose of this community service is to sacrifice qurban animals for takmirs of Surabaya City Mosque to provide "asuh" - thoyyiban meat, stress-free and bacterial contamination. The technique of selecting and maintaining qurban livestock is still not understood in accordance with the requirements of religion and animal welfare, thus impacting the absence of qurban animals and animal health, especially for skin diseases and disability, There is still a lack of understanding of the slaughter of qurban cattle to produce halal meat without causing stress, resulting in unhealthy meat quality, based on the color and pH of the meat, still does not understand the hygienes processing technique. So that it has the effect of producing meat that is not thoyyiban and contains contaminating bacteria, it still does not understand environmental sanitation after the slaughter of qurban animals. Training and simulation in the form of lectures on qurban selection techniques, maintenance, health, animal welfare, livestock slaughter, meat processing and distribution techniques, and halal slaughter of qurban animals by practicing directly at the Pegirian Animal Cut House in Surabaya. Participants' knowledge increased sharply after the distribution of materials from informants, during the ante and postmortem examinations, several types of diseases were found but medically harmless to human health, the process of managing and implementing qurban was good in accordance with the requirements of the Director General of Veterinary Public Health, Ministry of Agriculture, the quality of meat produced from the slaughter of qurban animals is quite good, although there are indications that animals experience severe stress before the slaughter, bacterial contamination is still within the threshold limits specified by SNI 3932:2008.